A Study on Business Strategy of Sime Darby energy - Liew Pek Ty, Betty (2009)
This study is about the overall performance of Sime Darby energy in the year of 2008 and the strategies implemented in business transactions. It also consists of the future plan of Sime Darby Energy in order to cater the internal customer, external customer and the stock holders.